Writings of Responsibility: Essay of a Global Approach Starting from the African Case. - (:unkn) unknown (My University, 2009)
This study dwells on the fact that, on one hand, men draw by themselves their historic trajectories and that, on the other, they develop as a result, a critical discourse which aims to be performative. It is the heterogeneous set of texts – novels, university researches, films, political speeches… – which embody this discourse that it labels as "writings of responsibility". Taking Africa as a case in point, the study intends to grapple with the modalities along which these writings address the question of responsibility. The study shows that this question is intimately linked to that of identity, which brings about some consequences. Besides, the needs of Realpolik which are not always connected with identity issues, also intend to inform the modalities whereby these writings are shaped. So, the question is how the writings of responsibility will react.Generally, whether these writings are about genocide, memory, reconciliation policies, about Africa or other places; they betray the coexistence of multiple positions and they contradict one another as well. For an example, the negationist texts cohabit with reconciliation discourses. The study concludes that, among the heterogeneous writings, some are capable of bringing constructive responses to the question of responsibility. To identify them and apply what they offer is just a question of will. It also concludes that Africa is not that unique as it seems: the writings that deal with this continent appear to behave like any other.
Keywords: African Research